Determination of the mass fraction of moisture of gum arabic - Terebylo, Olena; Brychka, Sergei; Podobiy, Olena (My University, 2021)
The main purpose of this study is to determine the mass fraction of moisture in the sample of gum arabic to confirm the data specified in the certificate of quality of the food additive.

Основною метою даного дослідження є визначення масової частки вологи у зразку камеді арабської для підтвердження даних, зазначених у сертифікаті якості харчової добавка.
Keywords: кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; gum arabic; mass fraction; drying; гуміарабік; масова частка; сушіння